MORFOMETRI GISIK KAWASAN PANTAI WISATA BAHARI SARIO KOTA MANADO - Zulkifli Otoluwa; Rignolda Djamaluddin; Royke M Rampengan; Jane Mamuaya; Esry T Opa; Joudy RR Sangari (JURNAL PESISIR DAN LAUT TROPIS, 2021)
Beach formation has an important role in protecting land from the action of the sea and it is useful for recreation, conservation and other uses. In â€œWisata Bahari Sarioâ€ Kota Manado coastal area there is still a particular area of beach that is used for various purposes, so it is important to study its morphology. This research was conducted with the aim of describing morphology and analyzing oceanographic factors that affected the dynamic process of beach morphology. The results showed that the beach had an area of 422.69 m2, with the criteria for short slopes in the Northeast and long slopes in the Southwest. The shapes of the beach surface were in the form of gutters and shoots, their appearance was more visible towards the Southwest. In general, the deposition process took place more intensively in the Southwestern part of the beach. Keywords: Beach, Morphology, Slope, Deposition